If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 83 Reorder the terms: 5 + 3x = 83 Solving 5 + 3x = 83 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = 83 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 83 + -5 3x = 83 + -5 Combine like terms: 83 + -5 = 78 3x = 78 Divide each side by '3'. x = 26 Simplifying x = 26
| 1+1u=5 | | 23x-2+2x=56 | | 2x^2=23x+39 | | -84x-96=-18x+60 | | 7p-3=-17 | | x^2=-50 | | 10v^5-32v^4+6v^3=0 | | 6x+36=6 | | x^2+21x=100 | | 3y^2+26y+16=0 | | y=x^2+18x+86 | | 425*x+1=0 | | 2[t-(4t+15)+9]=2(t+6) | | 4x+x-4x=2 | | 3a-3=-6 | | 10x+8=13-2x | | 8y-2=4+5y | | 6x^3-17x^2-3x=0 | | (9x*9x)+6x-6=0 | | 5+9x=-49 | | (x*x)-6x+6=0 | | 3y^3-7y^2-18y+42=0 | | -2h+17-18=15h-7-10 | | -33=-22+11x | | X^2-2+x^2-2=180 | | -8p-10=-3 | | 2=-9+11x | | (y*y)-5y-19=6y+1 | | 81-49v^2=0 | | 3p-5p=18 | | -84+15r=3r | | 10x^2-9x-12=0 |